Implementation of Principal-Agent Relationship: Case Study Strategic Decision in Financing Policies - Verawati; Saraswati, Erwin; Adib, Noval (European Journal of Applied Sciences, 2024)
Strategic Decisions in the self-help housing finance assistance policiy create complexity both in the formulation and implementation processes. The failure to achieve the target for distribution of self-help housing financing assistance funds proves that strategic decisions have not accommodated the needs of stakeholders and policy implementation has not been effective. This research aims to describe problems that arise during the process of strategic decision making and it’s implementation and also identify necessary improvements. Using qualitative methods with a case study approach, data collection in this research was carried out using in-depth interviews and documentation studies. The research results show the formation of a principal-agent relationship between the Ministry of PUPR and stakeholders. Conflicts of interest in the strategic decision-making process are very clearly visible when the Ministry of PUPR faces various different goals (goals conflict) between the need for empowering financial and financing institutions, provision of houses that meet construction quality standards, financing schemes and product structures that suit market needs, and easy requirements, while still prioritizing conformity with other laws and regulations and mitigating the risk of utilizing government budget funds. Strategic decisions agreed upon under the influence of these conflicts of interest ultimately provide challenges in the policy implementation stage. In order to minimize agency conflicts that occur, improvements to policy and governance are needed.